Morality, Moral Development, Moral Upbringing - Chutorański, Maksymilian (INSTED: Interdisciplinary Studies in Education & Society, 2012)
The main target of the article is an attempt to draw a reflection on the theoretical contexts of moral upbringing. What was discussed in particular is the question of relations between morality, psychological concepts of moral development and possibilities of pedagogic influence. The priority was given to Kohlberg?s philosophical basis of a cognitive and developmental concept and other psychological concepts. Thanks to it, in the further part of the text, it was possible to reflect on problems connected with the normativity of moral upbringing.